Penyuluhan Dampak Pernikahan Dini Terhadap Kesehatan Biologis dan Psikologis Ibu dan Anak - Sri Astuti; Nurbaety Nurbaety; Nur Islamiyati (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Health education for adolescents is only carried out for children in schools without involving adolescent parents. The role of parents is very important in providing information every day as a reminder that can prevent factors that trigger children to associate freely and eventually marry early. Health Centers and Health Workers have provided Reproductive Health Education through schools, but this has not reduced the number of early marriages which are increasing every year. Increasing knowledge regarding the impact of early marriage on the biological and psychological health of mothers, namely by providing counseling in each sub-district in collaboration with government agencies to include the role of parents in conveying and reminding youth about the impact of early marriage. Based on the preliminary study, it was obtained data on the number of adolescents who married early and had given birth to 8 children, and experienced the biological and psychological impacts of implementing early marriages. The objective of this study was to provide counseling regarding the impact of early marriage on the biological and psychological health of mothers in Lampe Village, Rasana District, East Kota Bima. The activity method is carried out by making pre and posttest questions that are used to measure the level of knowledge before and after being given counseling. Based on the results of the assessment before (pretest) counseling given to adolescents and their parents in the Kelurahan, it was shown that 15 (100%) had less knowledge about the impact of early marriage and 15 (100%) of adolescent parents had low knowledge. and experienced an increase after counseling was carried out by conducting a reassessment (posttest) where the parents of teenagers who had less knowledge were 5 people (33,33%), enough 8 people (53,33%) and good 2 people (13,33%). And teenagers with less knowledge, namely less 3 people (20%), enough 10 people (66,66%) and good category 2 people (13,33%).